Comparison of the Efficacy of Nifedipine and Hydralazine in Hypertensive Crisis in Pregnancy - Zahra Rezaei; Fatemeh Rahimi Sharbaf; Mino Pourmojieb; Yashar Youefzadeh-Fard; Manijeh Motevalian; Zahra Khazaeipour; Sara Esmaeili (Acta Medica Iranica, 2011)
Intravenous hydralazine is a commonly administered arteriolar vasodilator that is effective for hypertensive emergencies associated with pregnancy. Oral nifedipine is an alternative in management of these patients. In this study the efficacy of nifedipine and hydralazine in pregnancy was compared in a group of Iranian patients. Fifty hypertensive pregnant women were enrolled in the study. A randomized clinical trial was performed, in which patients in two groups received intravenus hydralazine or oral nifedipine to achieve target blood pressure reduction. The primary outcomes measured were the time and doses required for desired blood pressure achievement. Secondary measures included urinary output and maternal and neonatal side effects. The time required for reduction in systolic and diastolic blood pressure was shorter for oral nifedipine group (24.0±10.0 min) than intravenus Hydralazine group (34.8±18.8 min) (P≤0.016). Less frequent doses were required with oral nifedipine (1.2±0.5) compared to intravenus hydralazine (2.1±1.0) (P≤0.0005). There were no episodes of hypotension after hydralazine and one after nifedipine. Nifedipine and hydralazine are safe and effective antihypertensive drugs, showing a controlled and comparable blood pressure reduction in women with hypertensive emergencies in pregnancy. Both drugs reduce episodes of persistent severe hypertension. Considering pharmacokinetic properties of nifedipine such as rapid onset and long duration of action, the good oral bioavailability and less frequent side effects, it looks more preferable in hypertension emergencies of pregnancy than hydralazine.